The Effect of Training, Career Development, Empowerment and Work Discipline on Job Satisfaction at Class I Airport Operator Unit of Mopah Merauke - Blasius Basa; Anita Erari; Made Yudhi Setiani (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect of training, career development, empowerment, and work discipline on employee job satisfaction at the Class I Airport Operator unit of Mopah Merauke. The research involved 102 employees at the Class I Airport Operator unit of Mopah Merauke as the research sample. Data were collected using a questionnaire and then tabulated and analyzed using multiple linear regressions with the aid of SPSS 21. The analysis proves that training, career development, and empowerment have a significant effect on job satisfaction, while work discipline has no significant effect on job satisfaction.